2017
DOI: 10.3390/jfmk2040034
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Physiology of Knee Stability

Abstract: Knee instability has been the focus of large number of studies over the last decade; however, a high incidence rate of injury still exists. The aim of this short report is to examine knee joint anatomy and physiology with respect to knee stability. Knee joint stability requires the integration of a complex set of anatomical structures and physiological mechanism. Compromising any of these structures leads to destabilisation and increased risk of injuries. This review highlights the structure and soft tissue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 54 publications
0
49
0
2
Order By: Relevance
“…A higher incidence of injuries occurs from either overuse or underuse of muscles responsible for movement of the knee joint in athletes and individuals who have sedentary lifestyles, respectively. The incidence rate of knee instability is very high among nonathletes (both young and old individuals), and numerous studies have been conducted over the last decade . For instance, in one in‐depth study conducted on professional footballers over 7 consecutive seasons, it was observed that knee instability contributed to the second‐highest injury rate after thigh injury .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A higher incidence of injuries occurs from either overuse or underuse of muscles responsible for movement of the knee joint in athletes and individuals who have sedentary lifestyles, respectively. The incidence rate of knee instability is very high among nonathletes (both young and old individuals), and numerous studies have been conducted over the last decade . For instance, in one in‐depth study conducted on professional footballers over 7 consecutive seasons, it was observed that knee instability contributed to the second‐highest injury rate after thigh injury .…”
mentioning
confidence: 99%
“…The incidence rate of knee instability is very high among nonathletes (both young and old individuals), and numerous studies have been conducted over the last decade. 1 For instance, in one in-depth study conducted on professional footballers over 7 consecutive seasons, it was observed that knee instability contributed to the second-highest injury rate after thigh injury. 2 Quadriceps tendon injuries have a high chance of occurring during routine physical activity, as the tendon is subjected to motorized weight bearing.…”
mentioning
confidence: 99%
“…Instability is a cause of dissatisfaction following TKR (Abulhasan and Grey, 2017;Bourne et al, 2010;Noble et al, 2005) and has been shown to be more significant during demanding activities (Davidson et al, 2013). Knee stability is influenced by the articular geometry, ligament integrity, muscular contraction and kinetic loading conditions of the joint.…”
Section: Motivationmentioning
confidence: 99%
“…Up to 25% of TKR patients remain dissatisfied with their surgical outcome (Dawson et al, 1998;Nam et al, 2014;Noble et al, 2005). Instability is a cause of dissatisfaction following TKR (Abulhasan and Grey, 2017;Bourne et al, 2010;Noble et al, 2005) and has been shown to be more significant during demanding activities (Davidson et al, 2013). Knee instability can be defined as an inability to maintain a single leg stance due to joint subluxation as a result of pathological laxity, or self reportedly as the sensation of buckling, shifting, or giving way of the knee (Felson et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation